A low‐profile circularly polarized transmitarray antenna using rotated cross dipole elements. Issue 3 (11th December 2019) - Zhong, Xianjiang; Lei, Zhiyong; Dong, Mianmian; Xiao, Qinkun
Abstract: A low profile circularly polarized (CP) transmitrarray using double‐layer cross dipole elements is presented in this letter. The proposed element exhibits an overall thickness of only 0.22λ0, which offers the advantages of light weight, easy fabrication, and low cost compared to conventional transmitarray elements. The transmission coefficient of the element is analyzed by Ansys HFSS, and the results show that the element manifests a high transmission rate and good CP performance. Then, by using angular rotation technique, transmitarray with this type of element is designed, fabricated, and tested. The size of the transmitarray is 6.6 × 6.6λ0 at the center frequency of 10 GHz. The measured peak gain is 22.5 dB at 9.5 GHz, resulting in an aperture efficiency of 36%. The measured 1‐dB gain and 3‐dB axial ratio bandwidths are 10.2% and 12%, respectively.